Simply brilliant powerful techniques to unlock your creativity and spark new ideas - Schroeder, Bernhard (New York AMACOM, American Management Association, 2017)
This book explains how to break out of your mental box, reignite natural curiosity, and move step by step through a set of exercises that help individuals and teams fuel creativity through tight deadlines and create more ideas in brainstorming sessions.--Publisher's website.
Keywords: Creative ability in business; Creative ability; Creative thinking; New products